Feminist Interventions in Motherhood Discourse: A Comparative Study of Moth Smoke and The Joys of Motherhood from a Radical Feminist Perspective - Mughal, Muneeba; Shafique Ahmed Mahar; Irfan Ali; Fozia Mahar (University of Chitral Journal of Linguistics and Literature, 2023)
The research paper examines a comparative study of the feminist interventions in motherhood discourses, such as Hamid’s "Moth Smoke" (2000) and Bauchi Emecheta’s "The Joys of Motherhood" (1979) through textual analysis. The analysis is conducted through the lens of De Beauvoir’s (1949) Radical Feminist perspective. Writings for women are the emergency need to strengthen and empower women as mothers, wives, and daughters; hence the current study helps to examine Pakistani and African fiction writings from two different societies, cultures, nations, and countries respectively. The main objective of the study is to analyze women’s status as mothers in the Ibo and Pakistani society through the lens of Radical Feminism. The research study is based on a non-empirical method which is useful for identifying and analyzing themes and patterns in existing research and the findings are controlled by theoretical exploration (Saunders, 2019). The study follows a comparative analysis of the selected texts; the comparative research design is utilized to analyze the similarities and dissimilarities of the original texts (Caramani, 2009). Finally, the study concludes on the self-scarifying attitude of the mother, its loneliness, its otherness, and marital affair, however, the oppression and brutality faced by mothers in the patriarchal culture of Africa and Pakistan are also highlighted. Additionally, the social and cultural insignificance and inequalities experienced by motherhood in both Societies. The study provides insights into solving motherhood problems and offers suggestions for improving the living standard of motherhood in two comparatively different societies.